Supervision in Islamic Management - Kusuma, Muh. Thoriq Aziz; Baidi, Baidi; Suharto, Toto; Amin, Chusnul; Putra, Dutha Bahari Esa Tyas Kurtubi; Ikhsan, Shafi’i; Sabari, Sabari; Ismudiono, Zaki Rakhmawan (Educational Studies and Research Journal, 2025)
The main problem addressed in this research is the challenges in implementing supervisory practices based on Islamic principles, particularly due to cultural barriers, lack of understanding, and conflicting values within diverse organizational settings. The objective of the study is to explore strategies for incorporating Islamic values into supervisory practices, focusing on decision-making, conflict resolution, and fostering collaboration. The research adopts a qualitative approach, utilizing a descriptive-analytic method. Data is gathered from literature on Islamic management principles, leadership studies, and empirical cases of supervisory practices in Islamic organizations. The study emphasizes the role of empathy, justice, and integrity in creating a positive work environment. The findings suggest that educating managers on Islamic ethical practices and promoting cultural competence can effectively overcome barriers to implementing Islamic supervisory principles. Integrating Islamic values into management practices improves organizational ethics, enhances employee satisfaction, and fosters a more inclusive and productive work culture.